Ethical leadership and the role of scholars. Issue 1 (2nd January 2018) - Poff, Deborah; Caldwell, Cam
Abstract : Purpose: The purpose of this paper is to discuss an interview with Dr Deborah Poff – world renowned Scholar, Ethics Scholar, Founder and Editor of major ethics journals, and a university leader – on ethical leadership and the role of scholars. Design/methodology/approach: This is a personal interview with a world renowned ethics scholar on ethical leadership. Findings: Being good when bad is easier and will be received better is an extremely tough thing to do. Leadership without integrity may work for you and sometimes for those around you, but in the long run, compromising on goodness trust and integrity is harmful. Originality/value: Dr Poff's ideas come from a lifelong study of leadership and ethics. Her writing is world renowned and of valuable information for all scholars of leadership and ethics.